Diversity of Butterflies (Hexapoda: Lepidoptera: Rhopalocera) Around Campus 4 of Universitas Ahmad Dahlan - Indra Putra, Ichsan luqmana; Putri, Tasya Aulia; Setiawan, Haris (Universitas Negeri Surabaya, 2021)
The conversion of land functions can result in a decrease of environmental quality, which can reduce the diversity of butterflies. This study aimed to determine the diversity level and to find the most abundant and less abundant butterfly species around campus 4 UAD. The sampling was done at campus area, vacant land, rice fields and housing sites. Each of these sites had 2 plots and consisted of 5 subplots, respectively. Sampling was carried out four times, which was done in the morning at 08.00 - 11.00 and in the afternoon at 15.00 - 17.00. Butterflies caught using a sweep net. The data were analyzed by inferential analysis, namely Pearson correlation test. The calculation of the diversity level of butterflies was carried out by calculating the importance value index, the diversity Shannon-Wiener index, and the Simpson dominance index. The results showed that the diversity level of Shannon Wiener index of butterflies around the campus 4 UAD showed a low level (0.67). The species of butterflies found around campus 4 UAD were Acraea violae, Aphrissa statira, Appias libythea, Appias olferna, Catopsilia pyranthe, Catopsilia Scylla, Danaus Chrysippus, Elymnias hypermnestra, Junonia almana, and Junonia atlites. The most abundant butterfly was C. pyranthe with 125 individuals whereas the least abundant was A. libythea with 1 individual. This suggested that the ecosystem around campus 4 UAD is disturbed category; causing instability of the diversity that exists, including butterflies.